Risk Savvy: How to make good decisions
Risk-taking is essential for innovation, fun, and the courage to face the uncertainties in life. Yet for many important decisions, we are often presented with statistics and probabilities that we don't really understand and we inevitably rely on experts in the relevant fields-policy makers, financial advisors, doctors-to analyse and choose for us. But what if they don't quite understand the way the information is presented either?How do we make sure we're asking doctors the right questions about proposed treatment? Is there a rule of thumb that could help choose the right partner?This entertaining book shows us how to recognize when we don't have all the information and know what to do about it. Gerd Gigerenzer looks at examples from every aspect of life to identify the reasons for our collective misunderstanding of the risks we face. He shows how we can all use simple rules to avoid being manipulated into unrealistic fears or hopes, to make better-informed decisions, and to learn to understand risk and uncertainty in our own lives.